The Blechnum occidentale (Blechnaceae, Polypodiopsida) species group in southern and southeastern Brazil - Dittrich, Vinicius Antonio De Oliveira; Salino, Alexandre; Monteiro, Reinaldo (Phytotaxa, 2015)
A taxonomic study of the Blechnum occidentale species group in southern and southeastern Brazil (Minas Gerais, Espírito Santo, Rio de Janeiro, São Paulo, Paraná, Santa Catarina, and Rio Grande do Sul) was carried out and eleven taxa were accepted (nine species, two hybrids). Four taxa are widely distributed in tropical America, three are widely distributed in South America, three are exclusive to southern South America, and one is restricted to Brazil. New records are presented for several taxa in states from southeastern Brazil, in other regions of the country, as well as in other countries. Taxonomic descriptions are presented for the whole genus and for all infrageneric taxa occurring in the study area as well as synonymies, lectotypifications, a new combination (Blechnum × leopoldense), a key for the identification of infrageneric taxa, comments and geographical distribution for each taxon.